Jesuit Rhetoric and Language Studies in Modern Shanghai - Wei Mo (Religions, 2022)
From the sixteenth century onwards, the Jesuit educational model, as well as the method of evangelization propounded by the same religious Order, have been relying on the mastery of certain rhetorical techniques and, notably, in strong linguistic competency. This contribution examines how the Jesuits in modern Shanghai understood and put into application their traditional focus on rhetoric in the semi-colonial context of the time. After having recalled how Jesuits engaged with Chinese language and discourse in the Ming and early Qing dynasties, we take the 1923 Catalogue of the Jesuit publications in the missionary enclave of Zi-ka-wei as a reference point so as to describe and assess a number of trends that we summarize as follows. A privileged relationship was maintained between Latin and ancient Chinese and a growing interest in the “margins” and the way to address them efficiently triggered a renewal of ethnographic and linguistic studies; specifically, the expertise developed in dialectology testifies to the change that was occurring in the way to rhetorically address hearts and minds.